The debate on staff language competences and the use of official languages in the Balearic Islands health system - Ballester Cardell, Maria; Marí Mayans, Isidor (Linguistic Minorities and Society, 2021)
The Spanish Constitution of 1978 and the Statute of Autonomy of the Balearic Islands of 1983 established the official nature of both Spanish and Catalan and entrusted public authorities with guaranteeing the right of citizens to use one or the other on an equal footing. Subsequent to the language legislation of 1986, the legal framework of Catalan has varied depending on the majority party that forms a government. The debate stirred up by these regulations demonstrates the difficulties in ensuring real equality between official languages, when social initiatives cannot translate into sufficient political support and the national political context is hostile. The article explores this debate and discusses recent regulations surrounding the official languages competencies of health system staff, from the direct experience of the authors, as members of two consultative institutions on legal and sociolinguistic matters. Keywords: language rights, official language, language competence, medical communication, health services

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

Welfare services from a minority perspective. Explaining satisfaction with language-based welfare services among Swedish-speaking Finns - Himmelroos, Staffan; Vento, Isak; von Schoultz, Åsa (Linguistic Minorities and Society, 2021)

Bilingualism in the health system: The Catalan case - Ibáñez Ferreté, Òscar-Adrià; Mestres i Farré, Neus (Linguistic Minorities and Society, 2021)
Catalan-speaking citizens living in Catalonia have full, formal rights to use their language with all of their region’s administrations. Nevertheless, the available information on the knowledge and use of Catalan by civil servants shows that health care is a weak spot for regional administrations, due to the difficulty in covering all medical specialties. Plataforma per la Llengua has undertaken research in the form of a survey with a sample of 1,600 Catalan inhabitants, to ascertain the level of satisfaction with the enforcement of linguistic rights in public health and determine the scope of a potential language promotion policy that would have health care staff initiate conversations in Catalan. Results of government surveys suggest that language use (by both patients and providers) in the health care system, compared with language use in other areas of public administration, demonstrates the limits of the current regional language promotion policies in Catalonia. Keywords: catalan, linguistic minorities, linguistic rights, health and social services, language competencies

The Basque paradigm shift: From legislative language policies to person-centred care - Montes Lasarte, Aitor; Arauzo, Xabier; Zarate Sesma, Jon (Linguistic Minorities and Society, 2021)
The Basque Country has two official languages, Basque and Spanish, the first being spoken by 37% of the population. The Basque Health Service has developed language schemes to fulfill the legal requirements. Currently, there is a vast transformational shift from legislative policies to an evidence-based, patient-centred care approach. This paper discusses three key issues which could enhance language appropriate care: the recording of patient’s preferred language; the Basque language care pathways as a suitable and effective approach for determining the language of service along the continuum of care; and bilingual electronic medical records, which bring to the fore the challenge of language barriers among professionals. Considering its bilingual human resources, it offers an opportunity for establishing compelling evidence about implementation. Keywords: patient-centred care, bilingual pathways, language appropriate care, preferred language, active offer

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

Rhetoric and reality: A critical review of language policy and legislation governing official minority language use in health and social care in Wales - Prys, Cynog; Hodges, Rhian; Roberts, Gwerfyl Wyn (Linguistic Minorities and Society, 2021)
A concerted attempt is being made by the Welsh Government to revitalize the Welsh language in Wales through language legislation and policy initiatives. This paper explores the political rhetoric and practical reality of these recent legislative developments, as they pertain to the health care sector. It offers a qualitative analysis of written evidence provided by key stakeholders during the consultation process on the new legally-binding requirements of Welsh Language Standards for health care providers in Wales. We argue that these meso-level service providers are critical linchpins within the health care system and that it is at the meso level that full tensions between the macro rhetoric and micro reality occur. This contribution highlights shortcomings and barriers to Welsh language service provision in health care in Wales and recommends the adoption of wide-ranging, holistic approaches to language planning that meet the language needs of patients outlined by the Welsh Government. Keywords: health and social care, language planning, minority language, Welsh, Wales